Does Religiosity Mediate Gen Z’s Cosmetic Product Purchase Decisions? - Yudha, Ana Toni Roby Candra; Haryono, Slamet (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
The size of the Gen Z segmentation, which reaches a range of 40 per cent in 2045 and the tendency to consume halal products, and the role of religiosity are interesting studies to be studied. With regard to this, the stimulus-organism-response (SOR) model is needed to see and analyse the credibility of the influncer and the role of religiosity in mediating the decision to purchase cosmetic products. This study was conducted with a quantitative approach of SemPLS method, with 100 respondents, most of whom are gen Z. This study found that the model obtained was valid, but the position of religiosity did not mediate the credibility of endorsers, popularity, and business ethics on purchasing decisions for cosmetic products. This is considered reasonable, considering that consumers use more rationality in deciding their purchases. In addition, the popularity, attractiveness, and credibility of endorsers increase the decision to purchase cosmetic products. Of course, in accordance with the findings, valuable input can be provided, especially in the halal beauty industry to continue to educate with improved marketing strategies and contribute to the theoretical literature of management and marketing science.